POLITENESS STRATEGIES USED BY ENGLISH TEACHER TO MOTIVATE STUDENT IN ENGLISH LEARNING - Putri Nurmalita Sari; Sugeng Edy Mulyono (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
This research politeness strategy used by an English teacher at Smp Islam Nurus Syamsi to motivate student in English learning. This research used pragmatic theory Politness and Interaction by George Yule. The method that is used in this research is Qualitative Description Analysis Method by theory of Sudaryanto, meanwhile for searching or searching and analyzing the data this research used theory by Mile and Huberman. The results of the study shows that the total of occurrences is 52 data which comes from 4 sub-strategies. Positive politeness, Negative Politenes, Bald On Record, Off Record and Say Nothing. Bald On Record is the most dominant politeness strategy used by the teacher than the other politeness strategy.